The impact of self-targeted subsidies on social welfare in Iran - Parinaz Koozehgar; Ghorban Mohammad Pourghaz; Seyyed Rafie Mousavi Ortaboulagi (Management Science Letters)
Society welfare plays essential role on supporting poor and low income deciles governments normally pay subsidies on different goods to decrease the prices and as a result, increase purchasing power. However, due to lack of a good target, the relatively rich and high income deciles benefit more than the poor from subsidies do. Therefore, it seems necessary to design self-targeted safety-net programs and targeted subsidies. The primary objective of this study is to investigate the welfare consequences of self-targeted subsidies. In other words, this study tries to find out whether or not transferring one unit of subsidies paid on the subsidized goods mostly used by the rich to the nonsubsidized goods mostly used by the poor improves social welfare. For this purpose, using Atkinson social welfare function, we calculated the change in social welfare caused by self-targeted subsidies. The results show that self-targeted subsidies increase social welfare. The extent of this increase is negatively related to inequality aversion parameter, while positively related to the share of nonsubsidized goods in low income deciles budget.